ANSWER
The solution is ![(-1,9)](https://tex.z-dn.net/?f=%28-1%2C9%29)
EXPLANATION
We want to solve the simultaneous equations
![y=-3x+6---(1)](https://tex.z-dn.net/?f=y%3D-3x%2B6---%281%29)
and
.
We substitute equation (2) in to equation (1), to obtain
![9=-3x+6](https://tex.z-dn.net/?f=9%3D-3x%2B6)
This has now become a linear equation in a single variable
.
We solve for x by grouping like terms.
![9-6=-3x](https://tex.z-dn.net/?f=9-6%3D-3x)
![3=-3x](https://tex.z-dn.net/?f=3%3D-3x)
We divide through by negative 3 to get;
.
Hence, the solution is ![(-1,9)](https://tex.z-dn.net/?f=%28-1%2C9%29)
Answer:
Step-by-step explanation:
3x + 2y = 6
2y = -3x + 6
y = -3/2x + 3.....slope here is -3/2 and y int is 3
-4x + 6y = 15
6y = 4x + 15
y = 2/3x + 5/2.....slope here is 2/3 and y int is 5/2
different slopes, different y int means exactly ONE SOLUTION
Answer: m= -9
Step-by-step explanation: First use distributive property, -4(m) is -4m and -4(3) is -12. Then you have -4m -12 =24. Then use 12 and add it to the other side of the equation, cause of the subtraction sign, 12+24=36. Then you have -4m=36. Then divide the 4 to get the m by its self. 36 divided by -4 is -9. Your answer is m=-9
Hope this helps :)
Answer:
y + 2 = 5(x - 4)
Step-by-step explanation:
the equation of a line in point- slope form is
y - b = m(x - a)
where m is the slope and (a, b) a point on the line
here m = 5 and (a, b) = (4, - 2), hence
y - (- 2) = 4(x - 4)
y + 2 = 5(x - 4) ← in point- slope form